Pengembangan Wakaf Perumahan bagi Keluarga Berpenghasilan Rendah di Perkotaan Indonesia: Development of Housing Waqf for Low Income Families in Urban Indonesia - Ema Saswita Cania; Yenni Samri Juliati (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
The housing crisis in Indonesia, especially in urban areas, is becoming an increasingly pressing issue. According to data from the Central Statistics Agency (BPS), in 2022, only around 60.66% of households will live in livable houses. The housing backlog reached 12.1 million household units, with an additional need for around 1 million units each year. This urbanization causes 56.7% of Indonesia's population to live in urban areas, worsening this situation. This research offers the development of a productive waqf model for Low Income Family housing programs involving synergy between waqf institutions, the government and the private sector. This research methodology uses a descriptive-qualitative approach, describing the phenomena, potential and challenges in implementing housing waqf. The results show that managing waqf through a productive waqf approach and direct waqf can create innovative financing solutions. However, successful implementation requires strengthening regulations, public education, and cross-sector collaboration between the government, waqf institutions, and the private sector. With professional and sharia-based management, waqf can become an important pillar in housing development for urban communities and support poverty alleviation in Indonesia.